1975
DOI: 10.1007/bf01408465
|View full text |Cite
|
Sign up to set email alerts
|

Fragment angular distributions from fission of238U,209Bi and197Au by 140-MeV4He Ions

Abstract: Abstract. The fission fragment angular distributions from reactions of 140-MeV 4He ions with 23sU, 2~ and 197Au have been studied. From the anisotropies in the angular distributions, values for Jeff, the effective moment of inertia at the fission saddle point, have been estimated and compared with results obtained at lower bombarding energies. The derivation of ~ff values has included corrections for the effects of incomplete fusion mechanisms on the orbital angular momentum distribution of the fissioning nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…If in the analysis of these light ion data the 2-wave distribution is modified to account for incomplete fusion, then Clark et a1. 9 has found for uranium-like nuclei a linear relationship between Kft and E}/ 2 where Ef is the excitation energy of the fissioning nucleus minus its saddle point energy. Also, in our study of the Kr + Bi fission fragment data 2 • 3 we found a linear relationship between K6 and E{/ 2 for the less fissile Ac-like nuclei.…”
Section: L:35°mentioning
confidence: 99%
“…If in the analysis of these light ion data the 2-wave distribution is modified to account for incomplete fusion, then Clark et a1. 9 has found for uranium-like nuclei a linear relationship between Kft and E}/ 2 where Ef is the excitation energy of the fissioning nucleus minus its saddle point energy. Also, in our study of the Kr + Bi fission fragment data 2 • 3 we found a linear relationship between K6 and E{/ 2 for the less fissile Ac-like nuclei.…”
Section: L:35°mentioning
confidence: 99%